Contribution of different characters to lactation milk yield of Sahiwal cattle-A path analysis approach - Naskar, S; Banik, S; Tomar, S S (The Indian Journal of Animal Sciences, 2011)
The path analysis for lactation milk yield (LMY) of 471 Sahiwal cattle maintained at the institute’s herd from 1980 to 2002, was done for individual lactations up to fifth lactation and for all the lactations combined together. The study showed that birth weight and age at first calving (AFC) had negligible effects. The variability in 305 days milk yield (305 dMY) and lactation length (LL) had explained most of the variability in LMY. Out of93.66% variability in LMY explained by 305 dMY, 61.40% was due to its direct effect. The service period (SP) had a total effect of 9.65% to the LMY. Nearly 96% variability in LMY was explained by the factors under study.